Technology Entrepreneurship (ENT600) Training kit / Abdul Zahier Ismail, Muhammad Syafiq khusairi and Mohamad Nizar Mohd Naim - Ismail, Abdul Zahier; khusairi, Muhammad Syafiq; Mohd Naim, Mohamad Nizar (2020)
Training Kit is a product contain electrical and mechanical component. The product can give electrical and pneumatic knowledge toward staff and engineer. This product can reduce company cost for sending their staff for training. Staff will able to troubleshoot problem of machine after train using this machine. Training Kit only a size of dinner table can put anywhere that suitable for training but must have current and air compressed supply.